Argentina and Brazil: fiscal harmonization and subnational sales taxation : State/provincial VAT versus state/provincial retail sales tax - Piffano, Horacio Luis Pablo (2007)
In this paper the problem of “Dual Sales Taxation in a Federal Country” is discussed; and, particularly, “Sub-national VAT versus Provincial Retail Sales Tax” in “Federal/Provincial Sales Tax Coordination”, essentially thinking over two federations -Argentina and Brazil– with different institutional characteristics. First, let me cite three blocks of basic references I recommend on this theme. In author’s alphabetic order, they are: 1) Bird, R. (2005), McLure, Jr., (2005) and Piffano (2003, 2005b) – for direct treatment of the issue -. 2) Cnosen (1987, 2002); McLure, Jr. (1997, 1999); and, Zodrow and Mieszkowski (2002) – about National VAT versus National Retail Sales Tax written when “fundamental tax reform” were discussed in USA - ; and, 3) Bird (1994, 1999); Bird and Gendron (1998, 2001); Keen and Smith (1996, 1999); McLure, Jr. (2000, 2005); Mintz, Wilson, and Gendron (1994), Piffano (1999b, 1999c, 2003, 2005b); and, Varsano (1995, 1999) – when Sub-national taxation and several variants of dual and/or provincial VAT were discussed -. Discussion on this theme is rather complex because, beyond the theory, few country’s experiences are at hand to corroborate theories. Only Canadian case is perhaps the best (good?) example and Brazilian case (the bad one?), apart from the limited example of Argentina and India cases (not so good). The rest of federal countries have only one tier sales taxation (federal, not state or provincial) -of VAT type with some kind of revenue or tax sharing mechanism-, and USA with no federal sales taxation (only states RST).